My pants are haunted : by Jamie Kelly - Benton, Jim (Benton, Jim, 2004)
Jamie Kelly writes in her diary about her new jeans, which seemingly cause events that affect both her popularity and her efforts to get close to the eighth cutest boy in school, Hudson Rivers.